The Development of Ethnoscience-Based Chemical Enrichment Book as a Science Literacy - Mariana Fitria; Asih Widi Wisudawati (Universitas Islam Indonesia, 2018)
ABSTRACT: This study aims to examine the characteristics and quality of chemical enrichment books based on ethnosciences as a source of science literacy learners. The research method used is Research and Development. Data collection using questionnaire method. Data analysis is done quantitatively and qualitatively. The result of research is in the form of chemical enrichment book based on ethnoscience with characteristics: (1) A5 print media, (2) raised 4 Javanese cultural themes especially Yogyakarta area consisting of Batik, Wayang Kulit, Merapi, and Dagger themes, (3) the theme in general, the transformation of science from indigenous science to scientific science, and the renewal steps that can be made based on the existing environmental or social facts in the theme, (4) developed by containing affective, cognitive, andpsychomotor domains. Assessment is performed using an assessment instrument that refers to the instrument B1 of the Center for Curriculum and Bookkeeping. Assessment by material experts, media experts, cultural experts, chemistry teachers, and students' responses were 83.33%, 90.9%, 60%, 84.30%, and 90%, respectively, with Good category (B), Very Good (SB), Enough (C), Very Good (SB), and Good (B), thus this chemical enrichment book deserves to be a source of science literacy by studentsKeywords: development, enrichment book, ethnoscience, javanese culture, literacy scienceReceived: 10 February 2018, 16 February 2018, Accepted: 24 February 2018